Predicting exercise capacity recovery immediately after mitral valve surgery. Issue 10 (2nd August 2019) - Lin, Yu‐Shan; Lin, Wei‐Hsuan; Tsai, Hui‐Yu; Huang, Hsin‐Yi; Kuo, Li‐Ying; Chen, Bo‐Yan
Abstract: Background: This study presents the exercise capacity of postmitral valve surgery patients and determines predictors capable of affecting recovery. Methods: A total of 302 patients with mitral regurgitation who had undergone mitral surgery at the Heart Center in Taiwan from 1 August 2013 to 31 December 2015 were included in the present study. Data related to specific predictors of operative outcome were collected, including demographic data, intraoperative factors, exercise tolerance, echocardiogram data, concurrent cardiovascular disease history, comorbidities, lifestyle risk factors, and surgery types. Postoperative exercise capacity was presented as peak oxygen consumption (VO2 ; mL of O2 /kg/min) determined by exercise tests 3 weeks after surgery. Subjects were separated into two groups: a preserved recovery (peak VO2 ≥ 65% of predicted VO2max ) group and a poor recovery group (peak VO2 < 65% of predicted VO2max ). Preliminary univariate analysis was performed to test for possible relationships between predictive variables and exercise capacity. An analysis of all items shown to be significantly different between the two groups was then subjected to multivariate logistic regression analysis. Detected differences with P < .05 were considered significant. Results: Among the 302 patients sampled, female sex (odds ratio [OR], 2.65; 95% confidence interval [95% CI], 1.58‐4.47), obesity (OR, 0.26; 95% CI, 0.10‐0.64), sedentary lifestyle (OR, 0.47; 95% CI, 0.28‐0.79), and high preoperative New York Heart Association Functional Classification level (OR, 0.52; 95% CI, 0.31‐0.87) were significant predictors of poor exercise capacity. Conclusions: Without complicated clinical procedures, physicians and medical teams could easily use these items of information to screen the exercise capacity of mitral valve surgery patients and prepare a suitable after surgery plan if needed or request a consultation as early as possible.